Preferred physical characteristics of lidocaine thin film for women with vestibulodynia - Silverstein, R. Gina; Cromeens, Martha Grace; Rowland, Caroline; Ogbansiegbe, Joseph A.; Mihas, Paul; Benhabbour, S. Rahima; Carey, Erin T. (Frontiers in Pain Research, 2023)
Introduction Vestibulodynia (VBD) is the most common cause of sexual pain in the United States, affecting up to 15% of reproductive-aged women during their lifetime with limited treatment options. The purpose of this study was to describe ideal physical characteristics of a vulvar film designed for insertional sexual pain in sexually active women with VBD. Methods Twenty women were recruited to participant in one of six, semi-structured 60-minute focus group discussions regarding treatment options for VBD. Heterosexual women, aged 18–51 years old with a diagnosis of vulvodynia, vestibulodynia or insertional dyspareunia fit the inclusion criteria. Those who reported no episodes of vaginal intercourse in the prior 18 months were excluded. A new vulvar film technology loaded with 50 mg of 5% lidocaine was introduced to the group. Participants took part in focus groups on a rolling basis depending on availability. Focus group discussions were audio-recorded and transcribed verbatim. Two study investigators coded the transcripts using inductive coding and merged their respective projects to resolve disagreements. We analyzed data related to each code to develop code clusters and higher-level primary topics regarding device preferences. Data related to each of these primary topics was analyzed to assess the range of participant attitudes and preferences and to identify patterns within each primary topic. Results One hundred and sixteen women were recruited, and twenty women were enrolled. The mean age for the participants was 33.3 years. Most women were educated with at least some college (93%), White (78.6%), married (75%), and had income greater than 100,000 (50%). Analysis of the focus group discussions identified five common topics addressed by participants: desired loaded medication, film size, film shape, film flexibility, and ease and accuracy of use. Concerns across topics included comfort, sexual spontaneity, and efficacy. Interest in loading the device with other acceptable medications or combination with lidocaine was independently noted in 2/6 (33%) of the focus groups. Discussion Mucoadhesive vulvar thin films may be an acceptable drug delivery system for insertional sexual pain for women with VBD.